Interpreting Bounded Rationality in Business and Industrial Marketing Contexts: Executive Training Case Studies - Woodside, Arch; Lai, W.; Kim, K.; Jung, D. (Taylor & Francis, 2009)
This article provides training exercises for executives into interpreting subroutine maps of executives’ thinking in processing business and industrial marketing problems and opportunities. This study builds on premises that Schank proposes about learning and teaching including (1) learning occurs by experiencing and the best instruction offers learners opportunities to distill their knowledge and skills from interactive stories in the form of goal-based scenarios, team projects, and understanding stories from experts. Also, (2) telling does not lead to learning because learning requires action—training environments should emphasize active engagement with stories, cases, and projects. Each training case study includes executive exposure to decision system analysis (DSA). The training case requires the executive to write a “Briefing Report” of a DSA map. Instructions to the executive trainee in writing the briefing report include coverage in the briefing report of (1) details of the essence of the DSA map and (2) a statement of warnings and opportunities that the executive map reader interprets within the DSA map. The length maximum for a briefing report is 500 words—an arbitrary rule that works well in executive training programs.Following this introduction, section two of the article briefly summarizes relevant literature on how humans think within contexts in response to problems and opportunities. Section three illustrates the creation and interpreting of DSA maps using a training exercise in pricing a chemical product to different OEM (original equipment manufacturer) customers. Section four presents a training exercise in pricing decisions by a petroleum manufacturing firm. Section five presents a training exercise in marketing strategies by an office furniture distributer along with buying strategies by business customers. Each of the three training exercises is based on research into information processing and decision making of executives operating in marketing contexts. Section six concludes the article with suggestions for use of this training case and for developing additional training cases for honing ‘executives’ decisionmaking skills. Todd and Gigerenzer propose that humans use simple heuristics because they enable adaptive behavior by exploiting the structure of information in natural decision environments. “Simplicity is a virtue, rather than a curse”. Bounded rationality theorists emphasize the centrality of Simon's proposition, “Human rational behavior is shaped by a scissors whose blades are the structure of the task environments and the computational capabilities of the actor”. Gigerenzer's view is relevant to Simon's environmental blade and to the environmental structures in the three cases in this article, “The term environment, here, does not refer to a description of the total physical and biological environment, but only to that part important to an organism, given its needs and goals.”The present article directs attention to research that combines reports on the structure of task environments with the use of adaptive toolbox heuristics of actors. The DSA mapping approach here concerns the match between strategy and an environment—the development and understanding of ecological rationality theory. Aspiration adaptation theoty is central to this approach. Aspiration adaptation theoiy models decision making as a multi-goal problem without aggregation of the goals into a complete preference order over all decision alternatives. The three case studies in this article permit the learner to apply propositions in aspiration level rules in reaching a decision. Aspiration adaptation takes the form of a sequence of adjustment steps. An adjustment step shifts the current aspiration level to a neighboring point on an aspiration grid by a change in only one goal variable. An upward adjustment step is an increase and a downward adjustment step is a decrease of a goal variable. Creating and using aspiration adaptation levels is integral to bounded rationality theory .